Prescribing for children – taste and palatability affect adherence to antibiotics: a review. Issue 3 (16th November 2011) - Baguley, Dave; Lim, Emma; Bevan, Amanda; Pallet, Ann; Faust, Saul N
Abstract : The taste of an antibiotic is often not taken into account by practitioners, although there is significant evidence to show palatability correlates strongly with adherence. Many parents will be familiar with the difficulties of convincing young children to take bitter, unfamiliar medicine. Certain drugs, for example flucloxacillin, are so unpalatable that they should not be prescribed as syrups without prior 'taste testing' in an individual child, while others, such as oral cephalosporins, are accepted very well although they are more expensive with a broader antimicrobial spectrum than may be strictly necessary. Palatability is important in the broader context of global child health as regards the successful treatment of malaria, HIV and dehydration. The hidden cost of poor adherence resulting treatment failure, complications and the development of drug resistance cannot be over emphasised. Prescribing should involve parents, children and practitioners in an open discussion around the most suitable, palatable formulations for successful treatment outcomes.